A Tetraphenylbenzene‐Based AIE Luminogen with Donor‐Acceptor Structure: Unique Mechanochromic Emission and High Exciton Utilization. Issue 9 (1st September 2020) - Han, Pengbo; Lin, Chengwei; Ma, Dongge; Qin, Anjun; Tang, Ben Zhong
Abstract: Luminogens featuring aggregation‐induced emission characteristics (AIEgens) have been widely applied in high‐performance non‐doped blue organic light‐emitting diodes (OLEDs). However, AIEgens with high exciton utilization are rare. Herein, a tetraphenylbenzene (TPB)‐based AIEgen of PXZ‐TPB‐CN, in which phenoxazine (PXZ) and cyano (CN) serve as strong electron‐donating and withdrawing group, respectively, was rationally designed and facilely synthesized. PXZ‐TPB‐CN exhibits a unique mechanochromic luminescence. The lifetime of its ground powders and films exhibits a new decay component compared with the pristine powders, which attributes to the reverse intersystem crossing from the high‐lying triplet state process according to the theoretical calculation. To further verify this process, a non‐doped OLED using PXZ‐TPB‐CN as emitting layer was fabricated, and a much higher maximum external quantum efficiency (EQE) of the device than that of theoretical one was obtained, suggesting that triplet excitons are involved in a radiative process. In addition, the high horizontally oriented dipoles also contribute to this high EQE. This work provides a new strategy to realize blue AIEgen‐based OLEDs with high exciton utilization by attaching strong donors and acceptors on twisted AIE cores. Abstract : An AIEgen of PXZ‐TPB‐CN featuring donor‐π‐acceptor structure is rationally designed and facilely synthesized. This AIEgen not only exhibits remarkable enhanced and color‐tunable mechanochromic luminescence, but also high exciton utilization as proven by the non‐doped OLED using it as emitting layer, which might attribute to the reverse intersystem crossing from the high‐lying triplet state process.